(untitled) (Bioagro, 2026)
Heavy metals (HM) in agroecosystems represent an environmental concern posing risks to food safety. This study evaluated the presence of HM in irrigation water, agricultural soil, and cultivated plants (CP) within a peri-urban horticultural agroecosystem in Huanuco-Peru. A total of 19 random soil and CP samples, plus two water samples, were collected and analyzed in an laboratory accredited by the National Quality Institute (INACAL) . Results showed no contamination in irrigation water with a pollution load index (PLI) of 0.0006, whereas agricultural soil (PLI=7.42) and plant samples (PLI=1.70) exhibited contamination. The interaction between plant material and irrigation water revealed higher accumulation of Zn, Cd, Cr, and Pb, likely due to transport by dilution. In conclusion, both soil and plant components of the horticultural agroecosystem showed contamination by heavy metals, which is exacerbated by their mobilization through irrigation water. This process promotes the progressive accumulation of metals in the production system, posing a potential risk to the environment and public health.